Cancer risk by occupation and socioeconomic group among men : a study by The Association of Swiss Cancer Registries - Bouchardy, Christine; Schüler, Georges; Minder, Christoph; Hotz, Philippe; Bousquet, Arnaud; Levi, Fabio; Fisch, Thomas; Torhorst, Joachim; Raymond, Luc (Helsinki, 2002)
"This study presents the results of the first systematic analysis of incidence data on socioeconomic and occupational variations of cancer risks in the Swiss cancer registries. Despite limitations linked to occupational definitions, lack of national coverage, and statistical approach, this study provides interpretable results for additional research and public health surveillance."